The bases and methodology of deep ecology - Bombik, Mieczysław (Studia Ecologiae et Bioethicae, 2005)
The article includes the semantic analysis of basic terms and language phrases and synthetic depiction of following problems: the reformist organization of environmental protection, the sources of deep ecology, the basic theses of deep ecology, the political suggestions for solutions of environmental protection crisis, the organizational structures of deep ecology.